Circulating NKp46+ Natural Killer cells have a potential regulatory property and predict distinct survival in Non-Small Cell Lung Cancer. (1st February 2019) - Picard, Emilie; Godet, Yann; Laheurte, Caroline; Dosset, Magalie; Galaine, Jeanne; Beziaud, Laurent; Loyon, Romain; Boullerot, Laura; Lauret Marie Joseph, Elodie; Spehner, Laurie; Jacquin, Marion; Eberst, Guillaume; et al.
ABSTRACT: Natural killer (NK) cells are innate effector lymphocytes widely involved in cancer immunosurveillance. In this study, we described three circulating NK cell subsets in patients with non-small cell lung cancer (NSCLC). Compared to healthy donors (HD), lower rate of the cytotoxic CD56 dim CD16 + NK cells was found in NSCLC patients (76.1% vs 82.4%, P = 0.0041). In contrast, the rate of CD56 bright NK cells was similar between patients and HD. We showed in NSCLC patients a higher rate of a NK cell subset with CD56 dim CD16 − phenotype (16.7% vs 9.9% P = 0.0001). The degranulation property and cytokines production were mainly drive by CD56 dim CD16 − NK cell subset in patients. Analysis of natural cytotoxicity receptors (NCRs) expression identified four distinct clusters of patients with distinct NK cell subset profiles as compared to one major cluster in HD. Notably the cluster characterized by a low circulating level of NKp46 + NK cell subsets was absent in HD. We showed that the rate of circulating NKp46 + CD56 dim CD16 + NK cells influenced the patients' survival. Indeed, the median overall survival in patients exhibiting high versus low level of this NK cell subset was 16 and 27 months respectively ( P = 0.02). Finally, we demonstrated that blocking NKp46 receptor in vitro was able to restore spontaneous tumor specific T cell responses in NSCLC patients. In conclusion, this study showed a distinct distribution and phenotype of circulating NK cell subsets in NSCLC. It also supports the regulatory role of NKp46 + NK cell subset in NSCLC patients.